Empleabilidad en la economía informal, una investigación cualitativa con manicuristas de alta (2011)
This article is the report of a qualitative study which explores the psychosocial aspects related to the high employability of eight manicurists who work in the informal sector in the city of Cali, together with the reasons for their inclusion and permanence in this market. Method. Semi-structured interviews, including narrative, methodological and discoursive aspects, and analyzed by content analysis techniques and a conceptual map were used. Results. It was found that entering the informal sector was due to financial necessity, but continuing in it was a result of conviction (in spite of other possibilities in the formal sector). The high employability of the participants is related to the identification and satisfaction of their clients, which goes beyond the painting of nails, self evaluation to improve the quality of their work, and developing learning strategies to continue at the forefront of their trade. Conclusions. The high employability of the manicurists is related . among other things . to the ability of the participants to take responsibility for their continuity in the labour market, by means of strategies . conscious or otherwise . which include good relationships with their clients and the benefit of their own ability to learn